Preparation method of iron-cobalt nano-alloy flexible thin film and product and application of iron-cobalt nano-alloy flexible thin film

By treating iron-cobalt nanoalloy particles in an inert gas environment and adding them to the film forming agent to form an iron-cobalt nanoalloy flexible film, the problem of insufficient flexibility of iron-cobalt alloy is solved, and a film preparation with high flexibility and high performance is achieved, suitable for electromagnetic shielding applications.

CN119905299APending Publication Date: 2025-04-29CHUANGYE NEW MATERIALS (SUZHOU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411818018.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art is difficult to improve the flexibility of iron-cobalt alloys, limiting their application in flexible and bendable devices.

Method used

By mixing the iron salt and the cobalt salt in water and adding a stabilizer to form a mixed liquid, then adding sodium borohydride and a silicon-containing compound to an inert gas environment, after stirring and heating treatment, silica-coated iron-cobalt nanoalloy particles were obtained, and added to the film-forming agent for stirring to form an iron-cobalt nanoalloy flexible film.

Benefits of technology

The preparation process has been simplified, and an iron-cobalt nano alloy flexible film with good flexibility and stable performance has been obtained. It is suitable for electromagnetic shielding films, expanding its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005182365180000011
    Figure HDA0005182365180000011
  • Figure HDA0005182365180000012
    Figure HDA0005182365180000012
  • Figure HDA0005182365180000021
    Figure HDA0005182365180000021
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of nano-alloy flexible films, in particular to a preparation method of an iron-cobalt nano-alloy flexible film, a product of the iron-cobalt nano-alloy flexible film and application of the iron-cobalt nano-alloy flexible film. The preparation method of the iron-cobalt nano-alloy flexible thin film comprises the following steps that in an inert gas environment, sodium borohydride is added into a mixed solution to be stirred, a silicon-containing compound is added to be stirred, and a granular product is obtained; and cleaning and drying the granular product to obtain silicon dioxide-coated iron-cobalt nano-alloy particles, adding the silicon dioxide-coated iron-cobalt nano-alloy particles into a film-forming agent, uniformly stirring to obtain a mixture, smearing the mixture on a smearing plate, and airing to obtain the iron-cobalt nano-alloy flexible film. According to the preparation method of the iron-cobalt nano-alloy flexible thin film, the iron-cobalt nano-alloy flexible thin film with good flexibility and nanoparticle stability can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of nano alloy flexible films, and in particular to a preparation method of an iron-cobalt nano alloy flexible film, a product thereof and an application thereof. Background Art

[0002] Iron-cobalt alloys are widely used in traditional magnetic storage devices and sensors due to their excellent magnetic properties, such as high saturation magnetization, low coercive force and high magnetic permeability. They are also stable at high temperatures and their magnetism can be adjusted by changing the ratio of their components. They have great application potential, but their traditional form is rigid, which limits their use in flexible and bendable devices.

[0003] The Chinese invention patent with patent publication number CN108723383A discloses a controllable preparation method of iron-cobalt alloy magnetic nanoparticles with multiple morphologies and high saturation magnetic induction intensity, but does not provide a solution for improving the flexibility of the material.

[0004] Therefore, providing a method for preparing an iron-cobalt nanoalloy flexible film with nanoparticle stability is the main technical problem that needs to be solved at present. Summary of the invention

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing an iron-cobalt nano alloy flexible film, comprising the following steps:

[0006] S1. The iron salt and the cobalt salt are added to the water and mixed uniformly, and then a stabilizer is added and stirred to obtain a mixed solution;

[0007] S2. In an inert gas environment, sodium borohydride is added to the mixture and stirred, and then the temperature is raised and a silicon-containing compound is added and stirred to obtain a granular product;

[0008] S3. The granular product was washed with deionized water and then vacuum dried to obtain silica-coated iron-cobalt alloy nanoparticles;

[0009] S4. Add the silica-coated iron-cobalt nano-alloy particles into a film-forming agent and stir evenly to obtain a mixture, apply the mixture on a smear plate, and dry it to obtain an iron-cobalt nano-alloy flexible film.

[0010] In order to simplify the preparation method and obtain an iron-cobalt nanoalloy flexible film with stable performance, the inventors found during the experiment that by adopting the above-mentioned preparation method, a technical effect of simple preparation process, large-scale production, good repeatability and stable performance can be obtained.

[0011] In one embodiment, when a stabilizer is added to S1 and stirred and mixed, the temperature is raised to 50-70° C. and the stirring speed is 1-100 rpm.

[0012] In one embodiment, the temperature of stirring and heating when adding a stabilizer to S1 for stirring and mixing includes but is not limited to 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, and 70°C.

[0013] In one embodiment, when a stabilizer is added to S1 and the mixture is stirred and mixed, the temperature is raised to 60°C.

[0014] In one embodiment, the molar ratio of the iron salt to the cobalt salt is 1:(0.5-2).

[0015] In one embodiment, the molar ratio of the iron salt to the cobalt salt is 1:1.

[0016] In one embodiment, the iron salt in S1 is selected from a combination of one or more of ferric sulfate, ferrous nitrate, ferric nitrate, and ferric chloride; the cobalt salt in S1 is selected from a combination of one or more of cobalt chloride, cobalt sulfate, and cobalt nitrate.

[0017] In one embodiment, the iron salt in S1 is ferrous nitrate.

[0018] In one embodiment, the cobalt salt in S1 is cobalt nitrate.

[0019] In one embodiment, the molar ratio of the iron salt to the stabilizer is 1:(5-20), and the stabilizer comprises sodium propionate.

[0020] In one embodiment, the stabilizer is sodium propionate.

[0021] In one embodiment, the molar ratio of the iron salt to sodium propionate is 1:(5-20).

[0022] In one embodiment, the molar ratio of the iron salt to sodium propionate is 1:5.

[0023] In order to avoid the agglomeration of nanoparticles in the obtained granular product and improve the stability of the nanoparticles, the inventors found during the experiment that sodium propionate is used as a stabilizer and mixed with iron salt and cobalt salt in water, wherein the molar ratio of the iron salt to the cobalt salt is 1:(0.5-2), and the molar ratio of the iron salt to the sodium propionate is 1:(5-20). The use of sodium propionate can assist in the formation of small-sized nano-alloy particles. In the present application, sodium propionate is used relative to water-insoluble stearic acid surfactants such as oleic acid. The sodium propionate used in the present application has good water solubility, which can make the mixed solution have a higher acid radical ion concentration. The acid radical ions have electrostatic and coordination effects, and can be quickly anchored on the surface of the nano-alloy particles, limiting the growth and agglomeration of the nano-alloy particles, and further obtaining smaller nanoclusters, thereby improving the stability of the nanoparticles.

[0024] In one embodiment, the molar ratio of the iron salt to sodium borohydride is 1:(10-20).

[0025] In one embodiment, the molar ratio of the iron salt to sodium borohydride is 1:10.

[0026] In one embodiment, in S2, in an inert gas environment, an aqueous solution of sodium borohydride is added to the mixed liquid for 20-30 minutes and stirred at a speed of 1-100 rpm, and then the temperature is raised to 75-95°C and then a silicon-containing compound is added and stirred at a speed of 1-100 rpm to obtain a granular product.

[0027] In one embodiment, the temperature for further heating in S2 includes but is not limited to 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C, and 95°C.

[0028] In one embodiment, the molar concentration of sodium borohydride in the aqueous solution of sodium borohydride is 0.3 mol / L.

[0029] In one embodiment, the silicon-containing compound in S2 includes sodium silicate.

[0030] In one embodiment, after the temperature in S2 is raised to 85° C., a silicon-containing compound is added thereto and stirred to obtain a granular product; the silicon-containing compound in S2 is sodium silicate.

[0031] In one embodiment, the film former includes waterborne polyurethane and isopropyl alcohol.

[0032] In one embodiment, the film former is formed by mixing waterborne polyurethane and isopropyl alcohol.

[0033] In one embodiment, the volume ratio of the waterborne polyurethane to isopropyl alcohol is 1:(0.1-1).

[0034] In one embodiment, the volume ratio of the waterborne polyurethane to isopropyl alcohol is 1:0.1.

[0035] In one embodiment, the aqueous polyurethane has a viscosity of 50-150 mPa.s at 25°C.

[0036] In order to improve the dispersion uniformity and position stability of silica-coated iron-cobalt nano-alloy particles in the iron-cobalt nano-alloy flexible film, the inventors found in the experimental process that in an inert gas environment, an aqueous solution of sodium borohydride is added to the mixed solution for 20-30 minutes and stirred, and then the temperature is raised to 75-95°C and a silicon-containing compound is added and stirred to obtain a granular product. The silica-coated iron-cobalt nano-alloy particles are added to a film-forming agent formed by water-based polyurethane and isopropanol and stirred. The volume ratio of the water-based polyurethane to isopropanol is 1: (0.1-1). After stirring, the oxygen-containing groups on the surface of the silica in the silica-coated iron-cobalt nano-alloy particles can form hydrogen bonds and other interactions with the water-based polyurethane molecules, and the iron-cobalt nano-alloy particles are further fixed in position, and the displacement of the iron-cobalt nano-alloy particles in the silica-coated iron-cobalt nano-alloy particles can be prevented even under alternating magnetic field conditions.

[0037] In one embodiment, in S4, 1-3 g of silica-coated iron-cobalt nano-alloy particles are added to 0.5-2 mL of a film-forming agent and stirred to obtain a mixture, the mixture is applied on a smear plate, and dried at 25° C. to obtain an iron-cobalt nano-alloy flexible film.

[0038] The above-mentioned implementation manner can obtain an iron-cobalt nano alloy flexible film with good flexibility.

[0039] In one embodiment, in S4, 2 g of silica-coated iron-cobalt nano-alloy particles are added to 1 mL of a film-forming agent and stirred to obtain a mixture, the mixture is applied on a coating plate, the thickness of the mixture is 0.1 um-10 mm, and after drying at 25° C., an iron-cobalt nano-alloy flexible film is obtained.

[0040] In order to improve the durability of the flexibility of the iron-cobalt nano alloy flexible film, the inventors found during the experiment that by adding silica-coated iron-cobalt nano alloy particles to a film-forming agent and stirring the mixture evenly, the film-forming agent is formed by mixing water-based polyurethane and isopropyl alcohol; the volume ratio of the water-based polyurethane and isopropyl alcohol is 1:(0.1-1), the mixture is smeared on a smearing board, and the iron-cobalt nano alloy flexible film is obtained after drying. By using the above-mentioned water-based polyurethane and isopropyl alcohol as a film-forming agent, the durability of the flexibility of the iron-cobalt nano alloy flexible film can be improved, and the film is suitable for use as an electromagnetic shielding film in various electronic devices, thereby expanding the scope of application.

[0041] A second aspect of the present invention provides an iron-cobalt nano alloy flexible film, which is prepared by the above-mentioned method for preparing an iron-cobalt nano alloy flexible film.

[0042] A third aspect of the present invention provides an application of an iron-cobalt nano alloy flexible film, wherein the iron-cobalt nano alloy flexible film is applied in the field of electromagnetic wave absorption technology.

[0043] The iron-cobalt nano alloy flexible film has an iron-cobalt alloy content of 30% to 40%, and can be used as an electromagnetic shielding film in various electronic devices.

[0044] Beneficial Effects

[0045] 1. The method for preparing the iron-cobalt nano alloy flexible film provided by the present invention can simplify the preparation method, enable large-scale production, and have good repeatability and stable performance.

[0046] 2. Through the preparation method of the iron-cobalt nano alloy flexible film provided by the present invention, an iron-cobalt nano alloy flexible film with good flexibility can be obtained.

[0047] 3. According to the preparation method of the iron-cobalt nano alloy flexible film provided by the present invention, the iron-cobalt nano alloy particles coated with silicon dioxide are added to a film-forming agent and stirred to obtain a mixture, wherein the film-forming agent is formed by mixing water-based polyurethane and isopropyl alcohol; the volume ratio of the water-based polyurethane and isopropyl alcohol is 1:(0.1-1), the mixture is smeared on a smearing plate, and the iron-cobalt nano alloy flexible film is obtained after drying. By using the above-mentioned water-based polyurethane and isopropyl alcohol as a film-forming agent, the flexibility and durability of the iron-cobalt nano alloy flexible film can be improved, and the film is suitable for use as an electromagnetic shielding film in various electronic devices, thereby expanding the scope of application.

[0048] 4. The method for preparing the iron-cobalt nano alloy flexible film provided by the present invention comprises the following steps: adding an aqueous solution of sodium borohydride to a mixed solution in an inert gas environment for 20-30 minutes and stirring the mixture; heating the mixture to 75-95° C. and then adding a silicon-containing compound and stirring the mixture to obtain a granular product, thereby obtaining silicon dioxide-coated iron-cobalt nano alloy particles; adding the silicon dioxide-coated iron-cobalt nano alloy particles to a film-forming agent formed by waterborne polyurethane and isopropanol and stirring the mixture; the volume ratio of the waterborne polyurethane to isopropanol is 1:(0.1-1); after stirring, the oxygen-containing groups on the silicon dioxide surface of the silicon dioxide-coated iron-cobalt nano alloy particles can interact with the waterborne polyurethane molecules to form hydrogen bonds and the like; and further fixing the position of the iron-cobalt nano alloy particles, thereby preventing the displacement of the iron-cobalt nano alloy particles in the silicon dioxide-coated iron-cobalt nano alloy particles even under alternating magnetic field conditions.

[0049] 5. The preparation method of the iron-cobalt nano alloy flexible film provided by the present invention adopts sodium propionate as a stabilizer and mixes it with iron salt and cobalt salt in water. The molar ratio of the iron salt to the cobalt salt is 1:(0.5-2), and the molar ratio of the iron salt to the sodium propionate is 1:(5-20). The use of sodium propionate can assist in the formation of small-sized nano alloy particles. The sodium propionate used in this application has good water solubility relative to the water-insoluble stearic acid surfactants such as oleic acid. The sodium propionate used in this application has a higher acid radical ion concentration in the mixed solution. The acid radical ions have electrostatic and coordination effects, and can be quickly anchored on the surface of the nano alloy particles, limiting the growth and agglomeration of the nano alloy particles, and further obtaining smaller nano clusters, thereby improving the stability of the nano particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is the X-ray photoelectron spectrum of the silicon dioxide-coated iron-cobalt nano-alloy particles provided in Example 1.

[0051] Figure 2 This is a SEM image of the silica-coated iron-cobalt nano-alloy particles provided in Example 1.

[0052] Figure 3 This is the SEM image of the iron-cobalt nanoalloy flexible film provided in Example 1.

[0053] Figure 4 This is a diagram showing the appearance of the iron-cobalt nano alloy flexible film provided in Example 1.

[0054] Figure 5 This is a diagram showing the appearance of the iron-cobalt nano alloy flexible film provided in Example 1 after folding. DETAILED DESCRIPTION

[0055] Example 1

[0056] A first aspect of the present embodiment provides a method for preparing an iron-cobalt nano alloy flexible film, comprising the following steps:

[0057] S1. The iron salt and the cobalt salt were added to the water and mixed uniformly, and then a stabilizer was added and stirred to obtain a mixture, wherein the stirring speed was 50 rpm;

[0058] S2. In an inert gas environment, sodium borohydride is added to the mixture and stirred, and then the temperature is raised and a silicon-containing compound is added and stirred to obtain a granular product;

[0059] S3. The granular product was washed with deionized water and then vacuum dried to obtain silica-coated iron-cobalt alloy nanoparticles;

[0060] S4. Add the silicon dioxide-coated iron-cobalt nano-alloy particles into a film-forming agent and stir to obtain a mixture, apply the mixture on a smear plate, and dry it to obtain an iron-cobalt nano-alloy flexible film.

[0061] In S1, iron salt and cobalt salt are added to water respectively and mixed evenly, and then a stabilizer is added and stirred and mixed, and the mixture is heated to 60° C. to obtain a mixed solution.

[0062] The iron salt is ferrous nitrate, and the cobalt salt is cobalt nitrate.

[0063] The stabilizer is sodium propionate.

[0064] The molar ratio of the iron salt to the cobalt salt is 1:1, and the molar ratio of the iron salt to sodium propionate is 1:5.

[0065] The molar amount of the iron salt added is 5 mmol, the molar amount of the cobalt salt added is 5 mmol, and the molar amount of the sodium propionate added is 25 mmol.

[0066] In S2, in an inert gas argon environment, an aqueous solution of sodium borohydride is added to the mixed liquid and stirred at a speed of 50 rpm. After heating to 85° C., a silicon-containing compound is added and stirred for 20 minutes at a speed of 50 rpm to obtain a granular product.

[0067] The time for adding the aqueous solution of sodium borohydride to the mixed solution in S2 is 25 minutes.

[0068] The molar concentration of sodium borohydride in the aqueous solution of sodium borohydride is 0.3 mol / L.

[0069] The molar ratio of sodium borohydride in the aqueous solution of the iron salt and sodium borohydride is 1:10.

[0070] The silicon-containing compound is sodium silicate.

[0071] In the S4, 2 g of silica-coated iron-cobalt nano-alloy particles are added to 1 mL of a film-forming agent and stirred to obtain a mixture, the mixture is applied on a coating plate, the thickness of the mixture is 1 mm, and the iron-cobalt nano-alloy flexible film is obtained after drying at 25°C.

[0072] The film former is formed by mixing waterborne polyurethane and isopropyl alcohol.

[0073] The volume ratio of the waterborne polyurethane to isopropyl alcohol is 1:0.1.

[0074] The CAS number of the ferrous nitrate is 14013-86-6.

[0075] The CAS number of the cobalt nitrate is 10141-05-6.

[0076] The CAS number of the sodium propionate is 137-40-6.

[0077] The CAS number of the sodium borohydride is 16940-66-2.

[0078] The CAS number of the sodium silicate is 1344-09-8.

[0079] The CAS number of the isopropanol is 67-63-0.

[0080] The waterborne polyurethane was purchased from Taixing Zhongfang Xingtai New Materials Co., Ltd., and the model number is PU186-2.

[0081] A second aspect of the present embodiment provides an iron-cobalt nano alloy flexible film, which is prepared by the above-mentioned method for preparing an iron-cobalt nano alloy flexible film.

[0082] A third aspect of the present embodiment provides an application of an iron-cobalt nano alloy flexible film, wherein the iron-cobalt nano alloy flexible film is applied in the field of electromagnetic wave absorption technology.

[0083] Performance Testing

[0084] The test results obtained through the following performance tests provide a detailed description of the technical effects that can be achieved by the specific implementation methods of this application.

[0085] 1. Micro testing

[0086] (1) The silicon dioxide-coated iron-cobalt nano-alloy particles provided in Example 1 were irradiated with X-rays by an X-ray photoelectron spectrometer to obtain an X-ray photoelectron energy spectrum, see Figure 1 .

[0087] pass Figure 1 It can be seen that the silicon dioxide-coated iron-cobalt nano-alloy particles provided in Example 1 contain iron and cobalt elements.

[0088] (2) The silicon dioxide-coated iron-cobalt nano alloy particles provided in Example 1 were scanned by a scanning electron microscope (SEM) to obtain a SEM image, see Figure 2 .

[0089] pass Figure 2 It can be seen that the iron-cobalt alloy in the silicon dioxide-coated iron-cobalt nano-alloy particles provided in Example 1 is coated with silicon dioxide.

[0090] (3) The iron-cobalt nano alloy flexible film provided in Example 1 was scanned by a scanning electron microscope (SEM) to obtain a SEM image, see Figure 3 .

[0091] pass Figure 3 It can be seen that the iron-cobalt nano-alloy particles coated with silicon dioxide in the iron-cobalt nano-alloy flexible film provided in Example 1 are uniformly dispersed in the film.

[0092] 2. Appearance status test

[0093] Observe the appearance of the iron-cobalt nano alloy flexible film provided in Example 1. Figure 4 The appearance of the iron-cobalt nano alloy flexible film provided in Example 1 is obtained by folding the film. Figure 5 .

[0094] pass Figure 4 It can be seen that the iron-cobalt nano alloy flexible film obtained in Example 1 is black. Figure 5 It can be seen that the iron-cobalt nano alloy flexible film provided in Example 1 can be folded to obtain a flexible state.

[0095] The content description provided in this application is illustrative and is not intended to limit the scope of this application to the above-mentioned embodiments. The above-mentioned implementation modes provided in this application are merely specific implementation cases for the inventive concepts provided in this application. Therefore, this application is not limited by the above-mentioned embodiments. Under the inventive concepts provided in this application, technical solutions obtained by supplementing or modifying the above-mentioned implementation cases of this application or replacing them in a similar manner should all fall within the scope of protection of the present invention.

Claims

1. A method for preparing an iron-cobalt nano alloy flexible film, characterized in that: The following steps are involved: S1. The iron salt and the cobalt salt are added to the water and mixed uniformly, and then a stabilizer is added and stirred to obtain a mixed solution; S2. In an inert gas environment, sodium borohydride is added to the mixture and stirred, and then the temperature is raised and a silicon-containing compound is added and stirred to obtain a granular product; S3. The granular product was washed with deionized water and then vacuum dried to obtain silica-coated iron-cobalt alloy nanoparticles; S4. Add the silica-coated iron-cobalt nano-alloy particles into a film-forming agent and stir evenly to obtain a mixture, apply the mixture on a smear plate, and dry it to obtain an iron-cobalt nano-alloy flexible film.

2. The method for preparing the iron-cobalt nano alloy flexible film according to claim 1, characterized in that: When adding a stabilizer to the S1 and stirring and mixing, the temperature is raised to 50-70°C.

3. The method for preparing the iron-cobalt nano alloy flexible film according to claim 1, characterized in that: The iron salt in S1 is selected from one or more combinations of ferric sulfate, ferrous nitrate, ferric nitrate, and ferric chloride; the cobalt salt in S1 is selected from one or more combinations of cobalt chloride, cobalt sulfate, and cobalt nitrate.

4. The method for preparing the iron-cobalt nano alloy flexible film according to claim 1, characterized in that: The molar ratio of the iron salt to the cobalt salt is 1:(0.5-2).

5. The method for preparing the iron-cobalt nano alloy flexible film according to any one of claims 1 to 4, characterized in that: The molar ratio of the iron salt to the stabilizer is 1:(5-20), and the stabilizer includes sodium propionate.

6. The method for preparing the iron-cobalt nano alloy flexible film according to claim 1, characterized in that: The molar ratio of the iron salt to sodium borohydride is 1:(10-20).

7. The method for preparing the iron-cobalt nano alloy flexible film according to claim 1, characterized in that: The S2 is heated to 75-95° C., and then a silicon-containing compound is added thereto and stirred to obtain a granular product.

8. The method for preparing the iron-cobalt nano alloy flexible film according to claim 1, characterized in that: The film-forming agent comprises waterborne polyurethane and isopropyl alcohol, and the volume ratio of the waterborne polyurethane to the isopropyl alcohol is 1:(0.1-1).

9. An iron-cobalt nano alloy flexible film, characterized in that: The iron-cobalt nano alloy flexible film is prepared by the method for preparing an iron-cobalt nano alloy flexible film as described in any one of claims 1 to 8.

10. An application of the iron-cobalt nano alloy flexible film as claimed in claim 9, characterized in that: The iron-cobalt nano alloy flexible film is used in the field of electromagnetic wave absorption technology.

Citation Information

Patent Citations

  • Controllable preparation method of ferrocobalt magnetic nanoparticles with various morphologies and high saturation magnetic induction intensity

    CN108723383A